Research informing practice: Current issues in gymnastics research injury, skill development, elite performer and fundamental movements - Irwin, G.; Hume, P.; Sands, W.; Fujihara, T. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The aim of this applied session is to explore four key themes relating to current research in gymnastics. The themes include Injury occurrence (Professor Patria Hume), Skill development (Professor Gareth Irwin), Working with the Elite Gymnast (Professor William Sands) and Fundamental movements in gymnastics (Dr Toshiyuki Fujihara). Each speaker will explore their area, as experts in this applied science, drawing on a body of research evidence and gymnastics practice to report findings that impact understanding and hence have the potential inform coaching. Research has previously demonstrated that a conceptual understanding of how a skill works biomechanically can provide a coach and clinician with knowledge of effective, efficient and safe technique development (Irwin et al., 2005). Bridging the gap between the fundamental axioms of science and real world practice is a key aim of the Societys approach to sports biomechanics. To achieve this bio-fidelity the approach must be one that is rich in ecological validly. Professor Hume will explore injury rates and current issues associated with biological failure due to technique and maturation. Professor Irwin will draw on research to outline the impact of technique selection on injury potential and skill development. Professor Sands will draw on his wealth of experience as a biomechanist and applied scientist working with Olympic gymnasts to highlight issues associated with this fundamental scientific role. Dr. Fujihara will complete the session by examining fundamental skills. His talk will focus on rotational mechanics and include practical considerations for circles on pommel horse including the influence of a suspension aid in the development of skill.